The Impact of Production Factor Utilization on Shallot Farming with Surjan Technology System on Sub–Optimal Land to Enhance Production Efficiency - ALIUDIN; Sariyoga, Setiawan; Supriyo Wibowo, Aris (Research on World Agricultural Economy, 2025)
This study aimed to determine the effect of production factor utilization on shallot production. Three production factors were investigated, including seeds, land area, and NPK fertilizer. The application of these production factors was implemented among farmers who used the Surjan cultivation technology system. This study employed a quantitative method with a descriptive approach. The sampling technique used was proportional stratified random sampling, with a total sample of 44 shallot farmers. The analysis used included multiple linear regression and the Cobb–Douglas production function. The results showed that the elasticity values of seed, land, and NPK fertilizer production factors were 0.223, 0.471, and 0.236, respectively. The analysis results indicated that the production elasticity values of each production factor, namely seeds, land, and NPK fertilizer, were positive but less than 1. This means that the addition of these three production factors still had a positive impact on increasing shallot production. Therefore, farmers could increase the use of seeds, expand land area, and add NPK fertilizer up to a certain limit. The overall elasticity value was 0.93, indicating that the three inputs could still be increased in use. In this condition, farmers could combine the use of these inputs to achieve optimal production. Additionally, the use of high–quality seeds and increasing the quantity per hectare was recommended. Land expansion could be achieved through extensification or by increasing the cropping index.